Board Games and Numeracy Literacy: A Study on Their Influence on Learning Outcomes in Islamic Junior High Schools - Lian Gafar Otaya; Nusrotul Bariyah; Herson Awar; Dwi Istiyani; Fatimah Djafar (Yayasan Keluarga Guru Mandiri, 2025)
This study aims to determine the effect of Kometika, a board game, on media and numeracy literacy, as well as its impact on the learning outcomes of students whose scope is limited to Madrasah Tsanawiyah. There are some problems related to numeracy literacy learning in Islamic schools (madrasahs), some of which are the result of Asesmen Kompetensi Madrasah Indonesia (AKMI) and the low interest in numeracy literacy, which affects the low learning output. The research method employed was a quantitative experiment utilizing treatment-by-level designs. The findings showed that the average scores of students who studied using the Kometika board game media were higher than those of students without the Kometika board game media. The numeracy literacy interest of students who studied using the Kometika board game media was higher than that of those who studied without it. There was an interaction effect between the use of Kometika board game media and students' interest in numeracy literacy in relation to the learning outcomes. This means that Kometika board game media and numeracy literacy interest are interdependent and affect learning outcomes; therefore, support from related stakeholders, such as the head of the madrasah and teachers, is urgently needed. This study makes a significant contribution to the field of educational media and numeracy literacy, particularly within the context of Islamic education institutions. The research expands current pedagogical strategies aimed at improving numeracy skills among Madrasah Tsanawiyah students.